Effectiveness and safety of oral anticoagulants in the treatment of acute venous thromboembolism: a comparative cohort study in France. (14th October 2021) - Bertoletti, L; Gusto, G; Khachatryan, A; Quignot, N; Chaves, J; Moniot, A; Mokgokong, R
Abstract: Background: RCT evidence has shown that direct oral anti-coagulants (DOACs) are at least as effective and safer in terms of bleeding, compared to vitamin K antagonists (VKAs) in the treatment of acute venous thromboembolism (VTE). Purpose: To compare the risks of recurrent VTE and of bleeding leading to hospitalisation, in patients treated with DOACs (each compared with VKAs) for acute VTE in a real-world setting. Methods: A retrospective cohort study of treatment-naïve adult patients with VTE (patients with active cancer were excluded) treated with a DOAC (apixaban or rivaroxaban) or VKA, from 2013 to 2018. The French national health data system (SNDS) was used. After propensity score (PS) matching for each DOAC-VKA comparison, risks of bleeding (defined as principal diagnoses of hospital stays), recurrent VTE, and all-cause mortality were compared at 6 months. Cox proportional-hazards regression was used to estimate adjusted hazard ratios of the endpoints. Results: 58137 treatment-naïve patients were included: 10775 (18.53%) VKAs, 10440 (17.96%) apixaban, and 36922 (63.51%) rivaroxaban. Patients initiating VKAs were older than those initiating apixaban or rivaroxaban (mean age in years: VKAs, 71; apixaban, 65; rivaroxaban, 60) and had a higher comorbidity burden (mean CCI score: VKAs, 1.55; apixaban, 0.91; rivaroxaban, 0.69). PS matched cohort sizes were: apixaban (n=7503) and rivaroxaban (n=9179). Crude risks of recurrent VTE per 100 patient-year (95% CI) were 4.99 (4.36; 5.70), 3.36 (2.88; 3.92) and 4.33 (4.03; 4.66) for VKAs, apixaban, and rivaroxaban respectively. For bleeding, the respective crude risks were 5.21 (4.57; 5.94), 1.84 (1.49; 2.28), and 2.64 (2.41; 2.90). For all-cause mortality, the respective crude risks were 12.23 (11.26; 13.27), 4.69 (4.11; 5.34), and 2.73 (2.49; 2.99). Adjusted hazard ratios for the endpoints are presented in the table. Conclusions: Apixaban was associated with a lower risk of recurrent VTE and bleedings requiring hospitalisation compared with VKAs. Similar trends in risk reduction for these outcomes were observed for rivaroxaban compared with VKAs but without reaching statistical significance. Both DOACs were associated with lower risk of all-cause mortality compared with VKAs. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): BMS/Pfizer alliance